Social Capital and Antenatal Care: A Multilevel Analysis of Uptake Among Pregnant Women in Kuningan, West Java - Rosid, Sultonnur; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Maternal and Child Health, 2025)
Background: Antenatal care (ANC) services are activities and or a series of activities that are carried out from the occurrence of the conception period until before the start of the comprehensive and quality delivery process provided to all pregnant women. This study aims to analyze the relationship between education, family income, social capital of pregnant women, and posyandu strata with the use of ANC in posyandu. Subjects and Method: The study is an observational study using a cross-sectional design. This study was conducted in Kuningan Regency, West Java with a population of all pregnant women, from May to June 2024. A sample of 201 pregnant women >6 months was randomly selected. The dependent variable is the use of ANC in posyandu. The independent variables in this study were maternal education, family income, social capital and posyandu strata. Data collection was carried out by interviews with respondents and assisted by questionnaires and analyzed by square test and multilevel multiple logistic regression model.        Results: ANC visit among pregnant women in posyandu increased with high maternal education (OR= 2.78; 95% CI= 1.25 to 6.18; p= 0.012), high family income (OR= 2.19; 95% CI= 1.05 to 4.57; p= 0.036) and strong social capital (OR = 4.43; 95% CI = 2.22 to 8.86; p <0.001). Multilevel analysis showed a strong contextual influence of posyandu (ICC 18.6%; p = 0.008). Conclusion: The use of ANC for pregnant women in posyandu increased with high maternal education, high family income and strong social capital. Multilevel analysis shows strong contextual influence of posyandu.